Effect of evaporative cooling on peel browning and quality of litchi (Litchi chinensis) - SHILPA, SHILPA; MAHAJAN, B V C; SINGH, NAVPREM; BHULLAR, K S; KAUR, SUMANJIT (The Indian Journal of Agricultural Sciences, 2021)
The present study was carried out during 2016-18 at Punjab Agricultural University Ludhiana to examine the effect of evaporative cooling (EC) on peel browning and postharvest quality of litchi fruit during cold storage. The litchi fruits cv. Dehradun were harvested at the physiological maturity and subjected to EC treatments for 2 h, 4 h and 6 h. The fruits without EC were kept as a control. Thereafter, fruits were packed in corrugated fiberboard boxes and stored in a walk-in-cold room maintained at 2-3°C temperature and 90-95% relative humidity. The fruit samples were analyzed at weekly interval till four weeks for various physiological attributes, biochemical traits and enzymatic activities. The application of evaporative cooling for 6 h maintained lower physiological weight loss (6.38%), retained higher firmness (106.1g force),TSS (16.96°B), acidity (0.26%), anthocyanins (0.19 ΔA/g FW) and total phenols (218.43 mg/100g) during storage. The browning index of fruits was observed to be 3 (1/4-1/2 surface area brown up to 14 days of storage) with 4 and 6 h exposure to EC. The fruits subjected to EC for 6 h also maintained the lower activities of polyphenol oxidase (PPO) and peroxidase (POD) activity as compared to control. The study exhibited the expediency of EC treatment (6 h) to maintain the acceptable peel colour and prolong the storage life of fruits for 14 days as compared to 7 days in case of control.